Parkin Exon Rearrangements and Sequence Variants in LRRK2 Mutations Carriers: Analysis on a Possible Modifier Effect on LRRK2 Penetrance - Paolo Solla; Antonino Cannas; Gianluca Floris; Maria Rita Murru; Daniela Corongiu; Stefania Tranquilli; Stefania Cuccu; Marcella Rolesu; Francesco Marrosu; Maria Giovanna Marrosu (Parkinson's Disease)
Mutations in LRRK2 represent the most common causes of Parkinson's disease (PD) identified to date, but their penetrance is incomplete and probably due to the presence of other genetic or environmental factors required for development of the disease. We analyzed the presence of parkin sequence variants (mutations or polymorphisms) and exon rearrangements in LRRK2 mutations carriers (both PD patients and unaffected relatives) in order to detect a possible modifier effect on penetrance. Eight families with nine PD patients with heterozygous LRRK2 mutations (identified within 380 Sardinian PD patients screened for the presence of the five most common LRRK2 mutations) and sixteen additional relatives were genetically investigated for the presence of LRRK2 and parkin mutations. No evidence was found for the presence of pathological parkin mutations or exon rearrangements in patients or not affected family members. Three single-nucleotide polymorphisms (SNPs) were identified both in patients and unaffected relatives but did not significantly differ between the two groups. These data provide no support to the hypothesis whereby such parkin gene mutations may be commonly implicated in possible effect on penetrance in LRRK2 mutation carriers.